2016
DOI: 10.1007/s12016-016-8531-1
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box O1 Regulates Macrophage Polarization Following Staphylococcus aureus Infection: Experimental Murine Data and Review of the Literature

Abstract: The functions of macrophages that lead to effective host responses are critical for protection against Staphylococcus aureus. Deep tissue-invading S. aureus initially countered by macrophages trigger macrophage accumulation and induce inflammatory responses through surface receptors, especially toll-like receptor 2 (TLR2). Here, we found that macrophages formed sporadic aggregates in the liver during infection. Within those aggregates, macrophages co-localized with T cells and were indispensable for their infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…(12) Previous studies in FoxO1 conditional knockout mice identified an important role of FoxO1 in macrophage polarization in the liver. (13) Furthermore, Rictor is one of the four predicted target genes of miR-192-5p in both humans and rodents. Therefore, the Rictor-Akt-FoxO1 axis may represent a key signaling pathway underlying miR-192-5pmediated M1 polarization and activation of macrophages in NAFLD.…”
Section: Approach and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(12) Previous studies in FoxO1 conditional knockout mice identified an important role of FoxO1 in macrophage polarization in the liver. (13) Furthermore, Rictor is one of the four predicted target genes of miR-192-5p in both humans and rodents. Therefore, the Rictor-Akt-FoxO1 axis may represent a key signaling pathway underlying miR-192-5pmediated M1 polarization and activation of macrophages in NAFLD.…”
Section: Approach and Resultsmentioning
confidence: 99%
“…(12) In macrophages, FoxO1 has been identified to regulate macrophage polarization and activation through up-regulating toll-like receptormediated signaling. (13,35) Our results suggest that miR-192-5p promotes an inflammatory response in macrophages at least partially through its negative regulation of the Rictor/Akt/FoxO1 signaling pathway.…”
mentioning
confidence: 78%
“…13 In line with these findings, our previous study showed that macrophage FoxO1 was important in promoting M1 macrophage polarization. 15 In this study, significantly higher activation levels of Akt and lower activation levels of FoxO1 were determined in the Kupffer cells of PTEN mKO mice (Supplementary Figure 6). Thus, it is possible that in PTEN mKO mice, PTEN deficiency enhanced Akt/FoxO1 signaling in macrophages.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, PTEN mKO mice showed significantly higher levels of phosphorylated Akt and FoxO1 compared with PTEN f/f mice ( P =0.0480 for p-Akt and P =0.0003 for p-FoxO1, Supplementary Figure 6). Considering that activated Akt signaling and thus inhibited FoxO1 signaling was involved in suppressing proinflammatory cytokine secretion and promoting M2-like polarization of macrophages, 13, 15 this result indicated that PTEN may regulate the polarization of Kupffer cells through downstream Akt/FoxO1 signaling pathway.…”
Section: Resultsmentioning
confidence: 93%
“…Besides FoxO1 also interacts with the Toll-like receptor 4-mediated inflammatory response 35 and regulates IL-10 secretion during classic activation in hyperglycemia 36 . In previous studies, we found that FoxO1 regulates macrophage polarization in infection and promotes the anti-tumor function of TAMs by upregulating major histocompatibility complex II (MHC-II) expression 37,38 . In this study, we focused on the transcriptional mechanism of macrophage metabolic reprogramming.…”
Section: Introductionmentioning
confidence: 99%